Quality of life of patients with vitiligo attending the Regional Dermatology Training Center in Northern Tanzania. (24th January 2013) - Kiprono, Samson; Chaula, Baraka; Makwaya, Cyprian; Naafs, Bernard; Masenga, John
Abstract: Background Vitiligo is an acquired, predominantly asymptomatic, depigmenting disorder with profound psychological effects. Methods This was a cross‐sectional study conducted at the Regional Dermatology Training Center in Moshi, Tanzania. All 88 patients with vitiligo older than 15 years of age who attended the skin clinic from October 2009 to April 2010 were recruited. Data were collected using a structured questionnaire, Dermatology Life Quality Index questionnaire (DLQI), and Vitiligo European Task Force form. Results Vitiligo moderately affects patient's quality of life, as indicated by a DLQI mean score of 7.2 ± 4.8. The mean age was 41 years with a male/female ratio of 1:1.7. The mean age of disease onset was 33.5 years (range 16–83 years); vitiligo vulgaris was the most common disease form seen ( n = 49). None of the factors considered were found to be significantly associated with impaired quality of life on multivariate analysis. The majority of patients (73.8%) perceived that their disease was moderate to severe in contrast to the clinical grading in which only 49.2% patients were classified as having mild disease. This difference in classification of disease severity was statistically significant (Fishers exact test = 0.001). Conclusion Patients with vitiligo of African descent have a moderate impairment of quality of life.